Feromonkutatás: mit hoz a holnap? - Szőcs, Gábor (GEORGIKON FOR AGRICULTURE, 2017)
Present-day pheromone research (chemical ecology) emerged from interactions of biological and chemical disciplines, around half a century ago. Soon, the compositions of sex pheromone of many moth species, regarded as important pests, have successfully been identified. This opened new perspectives to plant protection in monitoring pests and developing new, selective, environmental-sound methods. With technical developments, further studies included species from other taxa of insects, host plant kairomones, microorganisms, chemical communication of aquatic species, and pheromones of vertebrates. Insight was gained in the mechanism of perception, neuroanatomical aspects, and into biosynthesis and neurohormonal regulation of pheromone production. New trends have been directed to neuron networks, molecular genetic basis of evolution and electronic modeling. At the same time it is still awaited to reveal the chemical communication of many species, which, especially in case of invasive pests evoking public attention, is especially urging. Host plant kairomones may offer alternative approaches, however, successes are often hampered because of problems in obtaining synthetic compounds of high (isomeric and/or enantiomer) purity, required for evoking proper biological responses. Hungary has joined to international pheromone research for a long time. New pheromone identifications were followed by developments of traps for monitoring. This is a prosperous direction for the future, as well, especially when combining with neuroanatomical, molecular and phytochemical studies. International attention is reflected in the honor that the rights of organizing the 2018 Annual Conference of the International Society of Chemical Ecology went to Miklós Tóth, academician and to his team (Department of Applied Chemical Ecology of Plant Protection Institute, CAR, Budapest).